Writing to survive The private notebooks of Conrad Richter - Richter, Conrad frey50; Richter, Harvena (University of New Mexico Albuquerque, NM, 1988)
This book provides a rare glimpse into the creative process.
Of Fate and Obstruction -- Finding His Own Type of Story -- Plots and Outlines -- Primary Writing Principles -- Tensing the Mind -- Writing the Story -- The Novel Notebooks -- Characters and Conversations -- A New American Style -- A Rude Thesaurus -- Advice to Young Writers -- The Ever Writer.
Includes bibliographical references and index
Keywords: Richter, Conrad -- 1890-1968 -- Notebooks, sketchbooks, etc; Novelists, American -- 20th century -- Diaries